BN nanospheres functionalized with mesoporous silica for enhancing CpG oligodeoxynucleotide-mediated cancer immunotherapy. Issue 30 (19th July 2018) - Zhang, Huijie; Cheng, Ting; Lai, Li; Deng, Shuhao; Yu, Ruixi; Qiu, Lipeng; Zhou, Juan; Lu, Guozhong; Zhi, Chunyi; Chen, Jinghua
Abstract : BNNS@MS-NH2 spheres significantly enhanced CpG ODN-mediated antitumor immunity. Abstract : CpG oligodeoxynucleotides (CpG ODNs) possess strong immunostimulatory activity, which hold great promise in cancer immunotherapy. However, their therapeutic efficacy is largely limited due to nuclease degradation and poor cellular internalization. Efficiently delivering CpG ODNs into target cells is crucial to improve their therapeutic efficacy. Boron nitride nanospheres (BNNS) possess advantage as carriers for CpG ODNs. However, their poor aqueous dispersity and low CpG ODN loading capacity became a big obstacle for further applications. Herein, we develop amino group grafted, mesoporous silica (MS)-functionalized BNNS as novel nanovectors for CpG ODN delivery. Modification of BNNS with MS significantly improved the dispersity of BNNS and CpG ODN loading. BNNS@MS-NH2 exhibited no cytotoxicity and enhanced the delivery of CpG ODNs into macrophages. BNNS@MS-NH2 /CpG ODN complexes triggered enhanced immunostimulation and induced higher amounts of cytokines. Most importantly, BNNS@MS-NH2 /CpG ODN complexes induced bifurcated cytokines, which simultaneously simulated the secretion of IL-6, TNF-α and IFN-α. In contrast, CpG ODN and BNNS/CpG ODN complexes could not. The result of the Transwell plate assay suggested that BNNS@MS-NH2 /CpG ODN complexes were more effective in inhibiting cancer cell growth. Taken together, our findings provide a promising strategy for enhancing CpG ODN-mediated cancer immunotherapy.